PEMBERDAYAAN KADER POSYANDU DALAM INOVASI PANGAN LOKAL: NUGGET KACANG KEDELAI (Glycine max. L) UNTUK CEGAH STUNTING PADA ANAK: EMPOWERING POSYANDU CADRES THROUGH LOCAL FOOD INNOVATION: SOYBEAN NUGGET FOR PREVENTING STUNTING IN CHILDREN - Asih Imulda Hari Purwani; Mardiana Prasetyani Putri (PT. ROCE WISDOM ACEH, 2026)
Stunting remains a major public health problem in Indonesia, with a prevalence of 21.6%. This condition affects not only children’s physical growth but also their cognitive development, immune system, and quality of life in the future. One of the efforts to prevent stunting is through empowering posyandu cadres as agents of change in nutrition education and the utilization of local food. This community service activity aimed to strengthen the capacity of posyandu cadres in Patianrowo Village, Nganjuk Regency, through socialization and training on local food innovation based on soybean (Glycine max. L) in the form of nuggets as an alternative nutritious food for children. The methods included preparation, socialization on stunting and balanced nutrition, as well as hands-on practice in soybean nugget production. Evaluation was conducted through pre-test, post-test, practice observation, and focus group discussions. The results showed a significant improvement in knowledge, with the average pre-test score increasing from 55.2 to 82.7 in the post-test, and participation aspects indicated by observation scores rising from 68.0 to 88.5. The cadres successfully mastered soybean nugget processing techniques and demonstrated creativity by incorporating other local food ingredients. This activity effectively enhanced cadres’ skills and confidence in developing local food innovations, while also strengthening their role in stunting prevention. In the future, it is expected that this innovation can be sustainably adopted by the community to contribute to improving children’s nutritional status and reducing stunting rates in Patianrowo Village.